On the Southern Ocean CO2 uptake and the role of the biological carbon pump in the 21st century - Hauck, J.; Voelker, C.; Wolf-gladrow, D. A.; Laufkoetter, C.; Vogt, M.; Aumont, O.; Bopp, L.; Buitenhuis, E. T.; Doney, S. C.; Dunne, J.; Gruber, N.; Hashioka, T.; et al. (Global Biogeochemical Cycles, 2015)
We use a suite of eight ocean biogeochemical/ecological general circulation models from the Marine Ecosystem Model Intercomparison Project and Coupled Model Intercomparison Project Phase 5 archives to explore the relative roles of changes in winds (positive trend of Southern Annular Mode, SAM) and in warming- and freshening-driven trends of upper ocean stratification in altering export production and CO2 uptake in the Southern Ocean at the end of the 21st century. The investigated models simulate a broad range of responses to climate change, with no agreement on a dominance of either the SAM or the warming signal south of 44 degrees S. In the southernmost zone, i.e., south of 58 degrees S, they concur on an increase of biological export production, while between 44 and 58 degrees S the models lack consensus on the sign of change in export. Yet in both regions, the models show an enhanced CO2 uptake during spring and summer. This is due to a larger CO2(aq) drawdown by the same amount of summer export production at a higher Revelle factor at the end of the 21st century. This strongly increases the importance of the biological carbon pump in the entire Southern Ocean. In the temperate zone, between 30 and 44 degrees S, all models show a predominance of the warming signal and a nutrient-driven reduction of export production. As a consequence, the share of the regions south of 44 degrees S to the total uptake of the Southern Ocean south of 30 degrees S is projected to increase at the end of the 21st century from 47 to 66% with a commensurable decrease to the north. Despite this major reorganization of the meridional distribution of the major regions of uptake, the total uptake increases largely in line with the rising atmospheric CO2. Simulations with the MITgcm-REcoM2 model show that this is mostly driven by the strong increase of atmospheric CO2, with the climate-driven changes of natural CO2 exchange offsetting that trend only to a limited degree (approximate to 10%) and with negligible impact of climate effects ...